Physiological characterization of parents of sorghum mapping populations exposed to water-deficit stress - Enninful, Regina (Kansas State University, 2019)
Changing climate presents new challenges to agricultural production and global climate models project increased intensity and magnitude in water-deficit stress conditions in the future. This is especially challenging for the arid and semi-arid regions of the world, where sorghum forms an important component of the cropping system. The research objective was to characterize eleven genetically and geographically diverse sorghum Nested Association Mapping parental lines (Ajabsido, SC1103, SC265, P898012, SC35, Macia, SC283, SC1345, Segaolane, SC971 and RTx430 - the common parent) for shoot and root related physiological parameters during the vegetative and grain filling stages. Using a lysimeter based experiment in the greenhouse, water-deficit stress (55 % to 60 % field capacity) imposed for 15 days during the vegetative stage recorded significant variation between water-deficit stress and well-watered treatments for all physiological and agronomic traits regardless of the genotypic variance, except for rooting depth. The genotype by treatment interaction indicated stem height to be not only under genetic control but was subject to complex effects of the watering regimes. Transpiration efficiency and carbon isotope discrimination increased for water-deficit stressed plants. A significantly higher biomass partitioning to the roots was detected under water-deficit stress compared with the well-watered plants. In Ghana, another experiment focusing on the vegetative stage with two levels of water-deficit stress imposed on selected set of sorghum genotypes, recorded a greater decrease for shoot and root related traits under the more severe stress (50 % to 55 % FC; lasting for 21 days) than the moderate water-deficit condition (60 % to 65 % FC; lasting for 15 days). The mean cumulative water transpired (liters) during the 21 days period was 2.32 for the severe water-deficit stress, 6.88 for the moderate water-deficit stress, and 10.7 for the well-watered condition. In the grain filling experiments conducted in both the greenhouse and on the field, water-deficit stress induced variations in grain number and grain weight along different positions on the panicle among the tested genotypes. In this regard, differences in panicle positional grain number accounted for differences in panicle positional grain weight as the positional individual grain weight was not affected by the stress. Regardless of the watering treatments however, differences in grain numbers and grain weight among genotypes resulted from the diversity in panicle architecture other than grain filling dynamics. In both the greenhouse and field experiments, SC1103 did not record any significant difference between the watering treatment for all measured growth and yield traits. Spearman’s rank correlations indicated the ability to select for water-deficit tolerance traits in the greenhouse that would partially represent rankings on the field. Generally, performance of genotypes such as SC35 portrayed a higher level of tolerance to water-deficit stress whereas other genotypes such as SC971 depicted significantly higher level of susceptibility. Findings from this research is helpful for providing pathways to map genomic regions responsible for increased resilience to water-deficit stress.
Keywords: Sorghum; Vegetative; Grain-filling; Water-deficit; Stress; Drought